The low-mass end of the neutral gas mass and velocity width functions of galaxies in ΛCDM - Yaryura, Claudia Yamila (2016)
We use the high-resolutionAquarius cosmological darkmatter simulations coupled to the semianalytic model by Starkenburg et al. to study the HI content and velocity width properties of field galaxies at the low-mass end in the context of Λ cold dark matter (ΛCDM). We compare our predictions to the observed Arecibo Legacy Fast ALFA (ALFALFA) survey HI mass and velocity width functions, and find very good agreement without fine-tuning, when considering central galaxies. Furthermore, the properties of the dark matter haloes hosting galaxies, characterized by their peak velocity and circular velocity at two radial disc scalelengths overlap perfectly with the inferred values from observations. This suggests that our galaxies are placed in the right dark matter haloes, and consequently at face value, we do not find any discrepancy with the predictions from the ΛCDM model. Our analysis indicates that previous tensions, apparent when using abundance matching models, arise because this technique cannot be straightforwardly applied for objects with masses Mvir < 1010M⊙.